Roles of Beclin1 protein expression in cervical cancer: a meta-analysis and bioinformatics analysis - Guan-Ying Ma; Shuai Shi; Hong-Yan Ma; Zhi-Gang Zhang (Taylor & Francis Group, 2022)
AbstractBeclin1 is a key regulator of a family of autophagy-related proteins. The aim of our study was to elucidate the clinicopathological and prognostic significance of Beclin1 expression which is a positive regulator of autophagy in cervical cancer. The results showed that a total of 2682 patients were enrolled in 21 case-control studies. The results showed that, as for Beclin1 expression, significant differences were found in cervical cancer vs. normal cervical tissues (p<.00001) and cancer tissues with vs. no lymph node metastasis (p<.00001); tumour diameter no less than vs. less than 4 cm (p=.001), myometrial invasion depth no less than vs. less than 1/2 and FIGO I vs. II (p=.02); relationship between Beclin1 expression and prognosis of cervical cancer (p=.03). Kaplan-Meier's plotter showed that Beclin1 expression was negative. It was associated with overall, post-progressive and distant metastatic survival. According to the Oncomine database, Beclin1 mRNA expression in cervical cancer tissues was higher than that in normal tissues. Cox multivariate showed that lymph node metastasis and TNM stage were important factors affecting the survival time of patients. Beclin1 expression can be used as an indicator of prognosis in patients, and provide methods and ideas for prevention and treatment.